Industrial Engineering’s Speaking Problem in Learning English - Citra Siwi Hanayanti; Fujiono fujiono; Desi Puspitasari; Emi Nurniati (Kontribusia : Research Dissemination for Community Development, 2023)
Abstract This study aims to analyze the difficulties faced by industrial engineering college students. It also investigates the way they triumph over those troubles in learning speaking. This study employed descriptive qualitative research. The subjects of this study were the freshman of industrial engineering department at University of Madura who took English course. The data were gathered from the observation, questionnaire, and document. The findings of this study confirmed that industrial Engineering students faced some problems in learning English. They were fear of making mistake, shyness, anxiety, lack confidence and lack of motivation. This study is expected to be useful for other researcher to consider their student in learning English speaking. Keywords: Industrial Engineering, Speaking English Problem